Conhecimentos prévios : condição para uma aprendizagem significativa dos números decimais - Menegaz, Andresa Maria (My University, 2023)
This research sought to answer the following question: What is the importance of prior knowledge for students in the sixth year of elementary school to enhance meaningful learning about decimal numbers? Faced with this question, the general objective of the research was to identify the impacts of prior organizers for teaching decimal numbers to students in the 6th year of elementary school at a school in the municipal education network of Vacaria/RS, covering the conceptual construction of decimal numbers, as well as the development of the addition and subtraction algorithm, having as a fundamental principle the prior knowledge of them. When developing this investigation, it is understood that the teaching methods must enhance the construction of meanings for the one who learns and, therefore, the fundamentals to promote the interaction of previous knowledge with new concepts are found in David Ausubel's Theory of Meaningful Learning, thus enabling new connections in the student's cognitive structure. As a resource that facilitates meaningful learning, active learning based on problem solving was listed. The research pointed out that students who had in their cognitive structure understanding in relation to natural numbers satisfactorily demonstrated the conceptual construction of decimal numbers, as well as operations and problem solving. In view of this, it is inferred that for students to understand and learn to operate with decimal numbers, one of the essential prior knowledge is the set of natural numbers and the operations between their elements. [resumo fornecido pelo autor]
Esta pesquisa buscou dar resposta à seguinte questão: Qual a importância dos conhecimentos prévios, aos estudantes do sexto ano do Ensino Fundamental, para potencializar uma aprendizagem significativa sobre números decimais? Diante disso, a pesquisa teve por objetivo geral identificar os impactos de organizadores prévios para o ensino de números decimais aos educandos do 6º ano do Ensino Fundamental, de uma escola da rede de ensino municipal de Vacaria/RS, abrangendo a construção conceitual dos números decimais, bem como o desenvolvimento do algoritmo da adição e da subtração, tendo como princípio fundamental o conhecimento prévio dos mesmos. Ao desenvolver essa investigação, se entende que os métodos de ensino devem potencializar a construção de significados para aquele que aprende. É na Teoria da Aprendizagem Significativa de David Ausubel, que estão os fundamentos para promover a interação de conhecimentos prévios com novos conceitos, o que possibilita novas conexões na estrutura cognitiva do educando. Como recurso facilitador da aprendizagem significativa, se elencou a aprendizagem ativa baseada em resolução de problemas. A pesquisa apontou que os educandos que possuíam, em sua estrutura cognitiva, compreensão em relação aos números naturais, demonstraram de forma satisfatória a construção conceitual dos números decimais, bem como as operações e a resolução de problemas. Em vista disso, infere-se que, para que os educandos compreendam e aprendam operar com os números decimais, é necessário haver conhecimento no que tange à concepção dos números naturais. [resumo fornecido pelo autor]
Keywords: Matemática (Ensino fundamental); Aprendizagem; Matemática - Estudo e ensino; Mathematics (elementary school); Learning; Mathematics - Study and teaching